1991
DOI: 10.1128/aac.35.4.665
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the penem CP-65,207 and its separate stereoisomers in humans

Abstract: CP-65,207 is a new broad-spectrum penem antimicrobial agent that is a 1:1 mixture of two stereoisomers. Five minutes after a 10-min intravenous infusion of 1 g of CP-65,207 to volunteers, mean concentrations in serum were 33 ,ug of the R isomer per ml and 29 tig of the S isomer per ml. Following rapid distribution, half-lives of the isomers were 53 and 55 min, respectively. Concentrations in urine exceeded 800 ,ug of each isomer per ml. Recovery of the S isomer in urine (46%) was much greater than recovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Compounds in phase-III trials (Table 3, Fig. 4) Sulopenem (6) (CP-70,429), which is a synthetic thiopenem BL first developed by Pfizer (New York, NY, USA) in the 1990s [65][66][67][68], and its prodrug sulopenem etzadroxil (7) (PF-03709270; po) are being developed as treatments for G-ve infections by Iterum Therapeutics (Dublin, Ireland).…”
Section: Compounds Undergoing Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds in phase-III trials (Table 3, Fig. 4) Sulopenem (6) (CP-70,429), which is a synthetic thiopenem BL first developed by Pfizer (New York, NY, USA) in the 1990s [65][66][67][68], and its prodrug sulopenem etzadroxil (7) (PF-03709270; po) are being developed as treatments for G-ve infections by Iterum Therapeutics (Dublin, Ireland).…”
Section: Compounds Undergoing Clinical Evaluationmentioning
confidence: 99%
“…VenatoRx have revealed that cefepime-taniborbactam had a superior primary efficacy endpoint to the carbapenem meropenem (66) in this trial with a similar safety profile [328], and plan to submit an NDA to the US FDA in 2023 [329]. The taniborbactam (62) + cefepime (41) combination has activity against E. coli, K pneumoniae, carbapenemase-producing Enterobacterales and P. aeruginosa [330][331][332].…”
Section: β-Lactam/β-lactamase Inhibitor (Bl/bli) Combinations Undergo...mentioning
confidence: 99%
“… 10 Oral administration of the prodrug sulopenem etzadroxil demonstrates increased absorption whereas IV administration of sulopenem (comprised of the stable S isomer) leads to significant active concentration in the urine. 11 , 12 With activity against both Gram-positive and -negative species, sulopenem inhibits peptidoglycan cross-linking thus preventing bacterial cell wall synthesis. 13 , 14 Notably, susceptibility reports for this compound indicate activity against fluoroquinolone-resistant, ESBL-producing and MDR Enterobacterales.…”
Section: Introductionmentioning
confidence: 99%
“…The stereochemistries of the auxiliaries of 2 and 12 were opposite, which was also capable of having affected the hydrolysis rate. [33][34][35][36] The presence of an asymmetric center at the water-solubilizing moiety is generally avoided to reduce structural complexity, however, the stereochemistry of the substrate did affect the enzyme reaction, [37][38][39][40] suggesting that this feature may be significant. In our case, the asymmetric center in the water-solubilizing moiety, which was derived from a natural amino acid, may have adjusted the prodrug half-life while improving the water solubility.…”
Section: Resultsmentioning
confidence: 99%